Brasil como miembro no permanente del Consejo de Seguridad de las Naciones Unidas en el mandato 2010-2011 - Ruiz Ferreira, Carlos Enrique; Cunha Leite, Alexandre César (El Colegio de México A.C., 2015)
The goal of this paper is to analyze Brazil’s work as a non-perma- nent member of the United Nations Security Council during the 2010-2011 mandate, emphasizing its priorities and taking stock of key issues over this period: 1) the role of the minustah, 2) the Israel-Palestine conflict, 3) African questions, 4) reform of the Security Council, 5) the Brazil-Turkey-Iran nuclear agreement, 6) the position on Libya. The G4 alliance will be discussed with regard to Brazil’s strategy to acquire a permanent seat on the UN Security Council.